(untitled) (Plant Tissue Culture and Biotechnology, 2008)
Genetic variation and relationship among 28 mango germplasm were analyzed using Random Amplified Polymorphic DNA (RAPD). Out of 20 primers screened, four were selected, which gave 50 clear and bright fragments, out of which 48 fragments were considered polymorphic. The proportion of polymorphic loci and gene diversity values across all loci were 96% and 0.29, respectively. The UPGMA dendrogram based on genetic distance segregated the 28 mango germplasm into two main clusters. Sukul alone formed one cluster and the rest germplasm were grouped together into another cluster. Mallika and Amrapali cultivar pair was very close to each other with the highest intervarietal similarity index (87.30%) and lowest genetic distance (0.08). On the other hand, Sukul and Meghnath pair was more distant to each other with the lowest intervarietal similarity index (14.29%) and highest genetic distance (0.87). The results of the present study indicated that the RAPD analysis could be utilized by breeders for further improvement of mango varieties. Key words: Germplasm, Characterization, Mango, RAPD DOI = 10.3329/ptcb.v17i1.1123 Plant Tissue Cult. & Biotech. 17(1): 71-77, 2007 (June)